Leaving Familiarity Behind (Comparative & International Education Series, 2022)
It’s 1 am as I bellow out this epiphany to my travel companion, attempting to raise my voice above the incessant chatter and steady tune of live music that surrounds us. He is sitting on a short, embroidered stool just across the table from me, but my voice only makes it halfway before it’s swallowed up into the indistinguishable mixture of hums that fill the humid summer air. The small table between us is more nightstand than table, less than 2 feet high and about the same across, and yet despite its stature it is burdened by an assortment of curiously foreign and vibrantly alluring items.